APLICATION OF IN VIVO EXPOSURE TREATMENT OF AN AGORAPHOBIA WITH ANGOR CRISIS CASE - Botella Arbona, Cristina; Benedito Monleón, Mª Carmen (Anales de Psicología / Annals of Psychology)
This paper exposes the application of an in vivo exposure treatment, in the form of autoexposure with cotherapist, for a case of agoraphobia with panic attacks. The clinic history of the patient and the level of fear and avoidance, before, during, and after the treatment, are presented and discussed.